Evaluation of peripheral arterial occlusive disease by computed tomography angiography - K., Udhaya Kumar; Grover, Shabnam Bhandari; Jain, Sunil Kumar; Bansal, Sandeep; Prasad, Jagdish; Thukral, B. B. (International Journal of Research in Medical Sciences, 2016)
Background: Characterization of peripheral arterial occlusive disease (PAOD) can be performed with non-invasive angiography using computed tomography (CT). The present study was conducted to evaluate the CT angiographic spectrum of aortoiliac and the lower limb arterial disease in symptomatic patients of peripheral arterial occlusive disease (PAOD) and to classify the lesions according to the Trans-Atlantic Inter-Society Consensus II (TASC II). Methods: The study was carried out in the department of radio-diagnosis in collaboration with departments of cardiothoracic surgery, cardiology and surgery, Safdarjung Hospital and Vardhman Mahavir Medical College, New Delhi. 50 patients aged above 40 years presenting with symptoms and (or) signs of lower limb peripheral arterial disease were recruited into the study after evaluating the renal function. Patient’s clinical history, ABI index and categories of PAOD according to the classification of Fontaine was noted. CT angiography of aortoiliac and lower limb arteries was performed with Philips Brilliance 40 CT unit. The findings in each CT angiography were analysed in respect to site, number, nature and distribution of the lesions and classified individually according to the TASC II. Results: The patients included in the study were all more than 40 years of age. The age range in the study group was 42 years to 75 years. The majority (86%) were male patients. Smoking and dyslipidemia were found to be the main risk factors in our patients. 24% of patients had documentary evidence of ischemic heart disease. On grading with ABI majority of patients (58%) presented in the end stage of the disease (stage IV). On CT angiography, number of lesions detected was 157. 97.4% of lesions were either stenotic or occlusive and 2.54% are with aneurysm. Maximum number of patients had femoropopliteal lesions followed by aortailiac lesions. 14 Winslow pathways were found in 10 patients. Maximum numbers of femoropopliteal lesions (47.29%) belong to type D, type B lesions account for 50% of total aortoiliac lesions based on TASC II classification. Out of 50, 40 were made follow up. Among them 8 were managed with conservative treatment and remaining 32 managed with treatment based TASC II classification. Conclusions: CT angiography is a reliable noninvasive imaging method for the comprehensive and multi parameter evaluation of patients with PAOD. CT angiographic findings are a highly accurate basis for treatment decisions and planning.